2022
DOI: 10.56093/ijans.v92i9.124839
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic factors affecting pre-weaning growth and survival rate in Barbari kids under semi-intensive management system

Abstract: The effect of non-genetic factors on pre-weaning growth and survival performance in Barbari kids was assessed to maximize pre-weaning growth and survival rates. Performance records of 10,013 Barbari goats maintained at ICAR-Central Institute for Research on Goats, Makhdoom, Mathura, India, from 1995 to 2020 were analyzed for non-genetic factors. The effect of period and season of birth, type of births, sex of kids, parity of doe and dam’s 90- days milk yield were significant on birth weight and pre-weaning gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
(24 reference statements)
6
10
0
Order By: Relevance
“…Higher birth weight and growth rate in male kids at later ages attributed to vigorous behaviour of male in suckling on account of differential hormone influence resulted in greater access of milk up to weaning, whose impact last at later ages also. Present results were in agreement of those reported by Sanchez et al (1994) in Granadina graded goats, Singh and Rai (2006) in Barbari in farmers flock, Singh et al (2008) in Jamunapari, Patel and Pandey (2013) in Mehsana goat, Ofori and Hagan (2020) in West African dwarf goat.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Higher birth weight and growth rate in male kids at later ages attributed to vigorous behaviour of male in suckling on account of differential hormone influence resulted in greater access of milk up to weaning, whose impact last at later ages also. Present results were in agreement of those reported by Sanchez et al (1994) in Granadina graded goats, Singh and Rai (2006) in Barbari in farmers flock, Singh et al (2008) in Jamunapari, Patel and Pandey (2013) in Mehsana goat, Ofori and Hagan (2020) in West African dwarf goat.…”
Section: Resultssupporting
confidence: 93%
“…Fluctuation in body weight at birth over the periods was mainly attributed to variation in weight at first kidding, age at first kidding, multiple birth rates and use of sets of different sires over the periods along with other climatic factors. Body weight and litter size at birth were very important economic traits which not only affects weight gain at later ages but also survival rate and fertility in female (Singh et al 2008). Almost similar trend in body weight was observed with the advancement of age with respect to period of birth.…”
Section: Resultsmentioning
confidence: 70%
“…In this study, the majority of mortality in kids occurred during the first month of age (160/282, 56.74%), followed by the second (86/282, 30.49%) and third months (36/282, 12.77%). Similar results were observed in previous studies conducted on kids and lambs, where approximately 69% of all the pre-weaning mortality of kids [ 32 ] and approximately 50% of all the pre-weaning mortality of lambs [ 19 , 33 ] occurred during the first month of age. In this study, the data analysis showed that a higher KBW was significantly associated with a lower occurrence of postnatal mortality.…”
Section: Discussionsupporting
confidence: 91%
“…The litter size and KBW are considered to be other factors that affect the ADG during the pre-weaning period, as single-born kids had a higher ADG on average compared with multiple-born kids [ 18 ]. Additionally, a positive correlation was observed between the KBW and ADG during the aforementioned period [ 19 , 20 ]. This demonstrates the superiority of single-born kids in terms of their BW; thus, the pre-weaning growth rate may be attributed to the prenatal competition between fetuses for nutrients in the uterus [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mortality rate of triplet-quadruplet kids was recorded to be higher than that of the kids born as twins and single. This is in concurrence with findings of Singh et al, (2022). Higher survival of single born kid is probably due to higher availability of milk from the dam compared to twin and triplet born kids.…”
Section: Effect Of Litter Size On Goat Kid Mortalitysupporting
confidence: 89%